The proangiogenic potential of a novel calcium releasing biomaterial: Impact on cell recruitment. (1st January 2016) - Oliveira, Hugo; Catros, Sylvain; Boiziau, Claudine; Siadous, Robin; Marti-Munoz, Joan; Bareille, Reine; Rey, Sylvie; Castano, Oscar; Planell, Josep; Amédée, Joëlle; Engel, Elisabeth
Graphical abstract: Abstract: In current bone tissue engineering strategies the achievement of sufficient angiogenesis during tissue regeneration is still a major limitation in order to attain full functionality. Several strategies have been described to tackle this problem, mainly by the use of angiogenic factors or endothelial progenitor cells. However, when facing a clinical scenario these approaches are inherently complex and present a high cost. As such, more cost effective alternatives are awaited. Here, we demonstrate the potential of electrospun poly(lactic acid) (PLA) fiber-based membranes, containing calcium phosphate ormoglass (CaP) particles, to elicit angiogenesis in vivo, in a subcutaneous model in mice. We show that the current approach elicited the local expression of angiogenic factors, associated to a chemotactic effect on macrophages, and sustained angiogenesis into the biomaterial. As both PLA and CaP are currently accepted for clinical application these off-the-shelf novel membranes have great potential for guided bone regeneration applications. Statement of significance: In current bone tissue engineering approaches the achievement of sufficient angiogenesis, during tissue regeneration, is a major limitation in order to attain full tissue functionality. Recently, our group has found that calcium ions released by the degradation of calcium phosphate ormoglasses (CaP) are effective angiogenic promoters. Based on this, in this work we successfully produced hybrid fibrous mats with different contents of CaP nanoparticles and thus with different calcium ion release rates, using an ormoglass – poly(lactic acid) blend approach. We show that these matrices, upon implantation in a subcutaneous site, could elicit the local expression of angiogenic factors, associated to a chemotactic effect on macrophages, and sustained angiogenesis into the biomaterial, in a CaP dose dependent manner. This off-the-shelf cost effective approach presents great potential to translate to the clinics.